Reversible impairment of coronary flow reserve in acute myocarditis. (5th August 2018) - Kellermair, Joerg; Kiblboeck, Daniel; Blessberger, Hermann; Kammler, Juergen; Reiter, Christian; Steinwender, Clemens
Abstract: Objective: Acute myocarditis is accompanied by an impaired coronary microcirculation. These microcirculatory disturbances are not well defined, and data are derived from complex invasive measurements. Therefore, this study aimed to evaluate the inflammation‐induced microcirculatory dysfunction including its reversibility and association with markers of inflammation severity (extent of LGE on CMR imaging and laboratory markers of myocardial necrosis) using the noninvasive technique of echocardiographic CFR measurement. Methods: Patients (n = 14) with clinically suspected acute myocarditis in the absence of coronary artery disease were prospectively enrolled, and echocardiographic CFR was determined by measuring peak diastolic coronary blood flow velocity at rest (PDV1) and under adenosine‐induced hyperemia (PDV2) at baseline and 3‐month follow‐up. Results: Eight of 14 (57.1%) patients showed an impaired baseline CFR (PDV2/PDV1 < 2). These patients were characterized by higher levels of cardiac troponin T (0.55 ± 0.39 vs 0.18 ± 0.08; P = 0.008) and larger areas of LGE on CMR. At 3‐month follow‐up, CFR was normal in all patients. Conclusion: A reversibly impaired coronary microcirculation is a frequent finding in acute myocarditis and is associated with markers of inflammation severity. Echocardiographic CFR measurement represents a feasible and safe method for its assessment.